PERTANGGUNGJAWABAN PIDANA KASUS PENYEBARAN BERITA BOHONG LEWAT JEJARING MEDIA SOSIAL BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - MEILIDAR ZEBUA; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The development of information technology influences on the developed of the new modern crime that is hoax. Netizen feels freedom to their personal accounts. The sanctions is required forprovide shock therapy. Beside that, needless to undermine the spirit of freedom of expression in a democratic system. The purpose of this thesis, namely; First, criminal liability for cases of distributing hoax through social media networks. Second, the ideal effort to solve the case of distributing hoax through social media networks.This research is a normative juridical research. This research uses the literature study and data analyst as the main focus. This research describing deduction clearly and detail about a problem.The conclusion is, First, the criminal liability of cases of distributing hoax through social media networks must comply with all elements of crime listed in Article 28 paragraph (1). But, criminal liability does not materialize because the victims are passive and ignore their hoax case. Second, the ideal effort to solve this problem can be realized by involving the role of the Government and wide society. Include the social media network. Author's suggestion, First, there should be a separation of criminal sanctions between the maker and distributor of hoax because almost netizen quickly to choose share features if they find new information. Need to be add an explanation of Article 28 paragraph (1) regarding the loss of consumer considering the victims of the distributing hoax not only suffered material losses but most also non-material. Criminal liability will be effective if the victim also actively reported their cases of hoax. Second, the Government should thinking about the long term impact of facebook existence which has a negative impact on society. The main point is, literacy education to the community is the most basic thing. Every level of society must know how to use social media to appropriate.Keywords: Criminal Responsibility - Hoax - Social Media